Kesantunan Berbahasa dalam Surat Kabar Linggau Pos - Tri Astuti; Tri Wahyudi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
The objective of this study was to describe the level of language politeness in Linggau Pos newspaper. Samples of the study was opinion articles in Linggau Pos which was published in May until June 2017. Type of this study was descriptive quantitative. In collecting the data, the writer used documentation, listening, reading, and recording. The data were analyzed by using padan and precentage technique. The indicator of language politeness was based on Geoffrey Leechs concepts and theories. Based on the results of the study, it was found out that there were 49 sentences that obeyed and disobeyed the principle of language politeness. There were 28 sentences which disobey the rules. They were dominated by adherence to the maxim of wisdom. They obeyed the indicators to give beneficial by giving information to the listener and using indirect strategy to sue the listener to do something.While, there were 21 sentences which disobeyed the rules.They were dominated maxim of praise, which is to reduce the praise of others and give criticism to the listener. The Percentage of language politeness in opinion articles in Linggau Pos newspaper included in enough level because there were 57,14 percent of the total data belong to maxim of language politeness. Keywords: language politeness, opinion articles, Linggau Pos